Malay micro-entrepreneurs and state's regulatory role: A case of Penang, Malaysia - Omar, Muhamad Fuzi; Zulkifli, Khairul Syakirin; Mohd Adnan, Normala (Academy IRMBR, 2018)
Micro-entrepreneurs (MEs) in Malaysia suffer from a slow projection of growth especially in developing to larger business scale. This group is important for Malaysia to achieve the vision 2020. Concurring with this, the study aims to explain a factor that contributes to the progress of the Malay’s entrepreneur business. This factor is being established based on the factor analysis outcomes from a survey conducted in Penang. A total 300 questionnaires were obtained from different cohorts of Malays entrepreneurs. Based on the factor analysis, three factors were constructed to explain the demand made the Malay entrepreneurs for their business need. The regulatory role is the significant demands which consist of eight items.